A STUDY OF GASEOUS PRODUCTS OF MINERAL BASED INTUMESCENT FIRE RETARDANT COATING IN STRUCTURAL APPLICATION - ZOHARI, ZAIFUL IQMAL (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
This project presents the study of the gaseous products of mineral fillers based intumescent fire retardant coatings in order to develop the inorganic fillers based intumescent fire retardant coatings. The coatings were formulated using ammonium polyphosphate (APP) as acid source, expandable graphite (EG) as carbon source, melamine as blowing agent, zinc borate as additives and epoxy as a binder. The different types of fillers such as aluminum trihydrate (ATH), alumina and talc were used in the intumescent fire retardant coatings formulation. This coating was coated onto steel substrate and there were 6 samples (0 %, 1%, 2%, 3%, 4%, and 5%) of fillers composition were prepared. After the curing period, the coating was tested using Gas Chromatography Mass Spectrometry (GCMS) in order to characterize the gaseous products after decomposition. There was presence of the organic compounds as the gaseous products of the samples such as benzyl alcohol. The higher percentage of mineral fillers in the formulation gave off less concentration of the gaseous products and more environmental friendly. The comparison has been made between the highest percentage of mineral filler and study shows that ATH 5% is the best to be used among the mineral fillers. The samples were then tested in furnace chamber at 450oC. The chemical composition of residual char was determined using the X-ray Diffraction (XRD). There were presences of the boron oxide, graphite and boron phosphate which were stable at high temperature and helped to reduce the heat flow to the structural.